Evaluation of the relationship between maxillary posterior teeth and the maxillary sinus floor using cone-beam computed tomography - Yechen Gu; Chao Sun; Daming Wu; Qingping Zhu; Diya Leng; Yang Zhou (BMC, 2018)
Abstract Background Maxillary posterior teeth have close anatomical proximity to the maxillary sinus floor (MSF), and the race, gender, age, side and presence/absence of adjacent teeth may influence the mean distances between the root apices and the MSF. This study aimed to evaluate both the relationship between the maxillary posterior teeth and MSF, and the influence of adjacent teeth loss on the distance between the maxillary posterior roots and MSF. Methods Cone-beam computed tomography images were collected from 1011 Chinese patients. The relationship between the maxillary posterior teeth and the MSF was divided into three types: Type OS (the root apex extending below/outside the MSF), Type CO (the root apex contacting with the MSF), Type IS (the root apex extending above/inside the MSF). The minimum vertical distances between the maxillary posterior roots apices and the MSF were recorded. The correlations of the distances with gender and age were analyzed. The distances between the maxillary posterior root apices and the MSF with different types of adjacent teeth loss was evaluated. Results Type OS was the most common relationship of all posterior root apices (P<0.05). Type IS was highest in the palatal roots (PRs) of the maxillary first molars (MFMs) and the mesiobuccal roots (MBRs) of the maxillary second molars (MSMs) (24.8% and 21.6%) (P<0.05). The frequency of Type IS decreased with age except the premolar roots and PRs of the MSMs (P<0.05). The MBRs of the MSMs had the lowest distances to the MSF (0.8 ± 2.5 mm), followed by the distobuccal roots of the MSMs (1.3 ± 2.7 mm) and the PRs of the MFMs (1.4 ± 3.4 mm) (P<0.05). Age was an important influencing factor to the mean distances while gender had little effects. The distance between the maxillary second premolar root apices and the MSF decreased with the absence of adjacent teeth (P<0.05). Conclusions The maxillary molars showed greater proximity to the MSF than premolars. Age had significant impacts on the relationship between maxillary posterior roots and MSF. The absence of maxillary first molars will influence the proximity of maxillary second premolar root apices to MSF.